(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The emergence and development of global sociology advances to the forefront a set of uneasy questions. This article outlines the scope of some questions which, in the authors opinion, should be discussed before and during the coming ISA forum The Future We Want: Global Sociology and the Struggle for Better World which is to be held in Vienna next year. Each notion of this heading as well as the state-of-art in this relatively new and rapidly developing sociological field should be exposed to analysis and critical reflection in order to foster for the production of sociologically relevant knowledge. Some starting points and key questions related to the methodology and theory of the global sociology field are named and discussed. Such basic concepts as future, better world, who are We? as well as the possible types of future social order and how to define a social capital of the desired global world and its environmental dimensions are discussed. In conclusion the author put forward twelve theses which are the necessary requirements which the global sociology should to address and carefully analyze. In the authors view, problem-oriented and activist-oriented comparative researches, interdisciplinary stance and the processes of the emergence of new global actors should be at the top of the research agenda in this field.